2017
DOI: 10.1097/mpg.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Using Serum IgE Antibodies to Predict Esophageal Eosinophilia in Children

Abstract: Objectives Symptoms of eosinophilic esophagitis (EoE) are variable and can be nonspecific. Food-specific serum IgE antibodies are frequently found in EoE patients and are obtained using a widely available blood test. Our objective was to evaluate the ability of food-specific IgE antibodies to predict the presence of esophageal eosinophilia. Methods We reviewed 144 medical records for pediatric patients having esophageal biopsy and serum analysis for IgE antibodies to food (exploratory group). We performed lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Recently, our group has reported that IgE antibodies to food, specifically low- to moderate-titer sIgE to CM, is associated with EoE among children scheduled for esophagoscopy. 12,16,2527 Here we found that food sIgE levels were detected commonly in sera from the EoE cohort (76%), but interestingly, 36% of control children also had detectable sIgE to milk (Table I). Although mostly of low titer (0.10–2.0 IU/mL), values were greater in children with EoE than control children.…”
Section: Resultsmentioning
confidence: 59%
“…Recently, our group has reported that IgE antibodies to food, specifically low- to moderate-titer sIgE to CM, is associated with EoE among children scheduled for esophagoscopy. 12,16,2527 Here we found that food sIgE levels were detected commonly in sera from the EoE cohort (76%), but interestingly, 36% of control children also had detectable sIgE to milk (Table I). Although mostly of low titer (0.10–2.0 IU/mL), values were greater in children with EoE than control children.…”
Section: Resultsmentioning
confidence: 59%
“…As for the prick test, the negative predictive value of IgE testing in better than the positive one but concordance with symptoms is low. (19) Several studies showed that patients with low or undetectable IgE could respond to the eviction of incriminated food. Thus, recombinant humanized anti-IgE antibody (Omalizumab) seems ineffective to treat EoE.…”
Section: %)(13)mentioning
confidence: 99%
“…Several investigators have examined testing methods for identifying food allergies in EoE by using either percutaneous skin testing 23, 31, 3639 or serum specific IgE. 4043 Alternative methods for measuring food specific IgE including basophil activation test (BAT), Immuno Solid Phase Allergen CHIP (ISAC) have been studied. Potential methods for testing non-IgE methods include IgG4 or atopy patch testing.…”
Section: Introductionmentioning
confidence: 99%